Preliminary Study on Image Captioning for Construction Hazards - Wen-Ta Hsiao; Wen-Der Yu; Tao-Ming Cheng; Alexey Bulgakov (Engineering Proceedings)
Construction accidents are a major contributor to occupational fatalities. To tackle this issue, improved monitoring for hazard elimination is crucial. By introducing a deep-learning image captioning system, we identified hazards via closed-circuit television in construction sites. By leveraging Inception-v3 for feature extraction and the gated recurrent unit for caption generation, real-time hazard monitoring was enabled. Bilingual evaluation understudy scores were determined for continuous and effective hazard detection, helping construction managers enhance safety.